Optimalisasi Biaya Pelaksanaan Konstruksi Jalan Dengan Metode Logika FUZZY FIS Takagi-Sugeno Pada Proyek Jalan Trans Kalimantan Provinsi Kalimantan Utara - Febryan Nugraha; Alwafi Pujiraharjo; Ruslin Anwar (Rekayasa Sipil, 2018)
National development requires infrastructure as one of the driving wheel of economic growth. One of the main parts of infrastructure development is the construction of highways. Road construction requires many factors to consider before the development process begins, such as factors of materials, equipment, labor, time and cost. In practice, accurate calculations are needed in determining the required amount of each factor, since a slight mistake can cause losses on the part of the contractor that impact the low quality of the highway. In this research used fuzzy logic (fuzzy logic) as decision maker. Because the workings of fuzzy logic represent the way of human thinking that appears from the outside and contained in the form of words. Fuzzy logic is a logic that has the value of vagueness or fuzzyness between right and wrong. In fuzzy logic theory a value can be true or false at the same time. Fuzzy itself in the language is interpreted as or vague.Fuzzy logic has degrees of membership in the vulnerable 0 to 1. Fuzzy logic used as a pointer to the extent to which the value is true and the extent to which the value is wrong, in contrast to classical logic, a value has only two the possibility of being a member of the set or not. Fuzzy logic can also be used as an alternative decision-making as an easy modern control system. The fuzzy logic used is FIS Takagi-Sugeno because of its more efficient computing, works well for linear techniques, works well for adaptive optimization and ensures continuity of results. In this research will also be developed an application that aims to assist users in analyzing and forecasting the needs of what is required in making a highway construction. Using the Takagi_Sugeno FIS based FIS user interface generated in this research, the resulting performance using Fuzzy Logic is better than the manual calculation, it can be seen from the total cost generated from the calculation method. For calculations using Fuzzy Logic has a total cost of Rp.52.950.009.851 while the results of manual calculations of Rp. 54.840.926.051.